Effect of dietary replacement of crushed sorghum grains by bakery by-products on the laying hen performance (The Sudan Journal Of Animal Production المجلة السودانية للانتاج الحيواني, 2021)
Effect of dietary replacement of crushed sorghum grains by bakery by-products on the laying hen performance Nuha H. Talib1, Afaf A. Mabrouk1, I. I. Hamid1 and Buthina M. Rahma21 Animal Production Research Centre, Hillat Kuku- SUDAN2 Faculty of Animal Production, El ZaeemAlazhari University- SUDANSummary:This study was conducted to investigate the nutritive value of bakery byproducts inclusion and its effects on layer hen production performance.A total number of 36 Hisex white hens (32 weeks age) were weighed and distributed over 12 cages with almost the same egg production (EP) level among the cages. The experiment was conducted as a 3×4 complete randomized of treatments including three replacement levels (0, 20, and 40%) of sorghum grains with dried bakery byproducts (BP). The data collected included hen day egg production% (EP), egg weight (EW) and egg mass (EM g/hen/day), were calculated. Also egg characteristics were recorded. The results revealed that dietary inclusion of BP in layer hen diets exerted no negative effect on production performance namely EM, EP and EW (45.54, 45.33and 44.72; 85.48, 81.67 and 84.52; 53.26, 55.57 and 52.88 respectively) or egg characteristics.The conclusion drawn up from this study that BP could effectively replace up to 40% sorghum grains in layer hen diets without adverse effects on production performance or egg quality.
Keywords: Bakery by-products (BP); Sorghum grain replacement; Laying hens; Egg production (EP); Egg weight (EW); Egg mass (EM); Egg quality; Poultry nutrition; Alternative feed ingredients; Feed formulation